Rare targetable drivers (RTDs) in non-small cell lung cancer (NSCLC): Outcomes with immune check-point inhibitors (ICPi). (October 2018) - Dudnik, Elizabeth; Bshara, Elias; Grubstein, Ahuva; Fridel, Ludmila; Shochat, Tzippy; Roisman, Laila C.; Ilouze, Maya; Rozenblum, Anna Belilovski; Geva, Smadar; Zer, Alona; Rotem, Ofer; Allen, Aaron M.; et al.
Highlights: This article reports on ICPi efficacy in NSCLC with rare targetable drivers (RTD). In NSCLC with RTD, ICPi have favorable efficacy and independent impact on OS. Future research is needed to clarify the value of ICPi in each of the RTD subgroups. NSCLC with RTD have variable PD-L1 expression and TMB, and MSI stable status. Predictive value of PD-L1 expression/TMB in NSCLC with RTD remains to be determined. Abstract: Objectives: Efficacy of immune check-point inhibitors (ICPi) in NSCLC with rare targetable drivers (RTDs) is largely unknown. Materials and Methods: Consecutive patients with NSCLC and RTDs (non- EGFR / ALK, n-82) were selected from the Davidoff Cancer Center database. ORR, PFS, OS with ICPi, OS since advanced disease diagnosis, TMB, MSI, and PD-L1 expression were analyzed; uni- and multivariate PFS and OS analyses were done. OS with ICPi was compared between the RTD cohort and the non-selected NSCLC cohort (n-278). Results: Of 50 tumors tested, 32%, 38%, and 30% were associated with ≥50%, 1–49% and <1% PD-L1 expression, respectively. Median TMB (n-48) comprised 4 muts/Mb (0–57); TMB ≥ 10 muts/Mb was seen in 19% of tumors. Both TMB and PD-L1 expression varied across different RTDs. All the 47 tumors were MSI stable. ORR with ICPi (n-44) was 16%, median PFS was 3.2 months (95% CI, 2.6–5.0), median OS was 16.2 months (95% CI, 8.4-NR). No correlation was seen between OS with ICPi and PD-L1 expression (p > 0.4), TMB (p > 0.8), or RTD type (p > 0.3). In the multivariate analysis, ECOG PS (p-0.005), targeted agents exposure (p-0.005), and ICPi exposure (p-0.04) were the only variables which correlated with OS since advanced disease diagnosis. Median OS since advanced disease diagnosis comprised 32 months (95% CI, 19.9–44.9) and 13 months (95% CI, 6.6–15.9) for patients who were and were not exposed to ICPi, respectively (log-rank test-6.3; p-0.01). In the inter-cohort comparison, for patients matched for ECOG PS (0/1), median OS with ICPi comprised 17.5 months (95% CI, 8.1-NR) and 8.6 months (95% CI, 6.7-NR) for RTD and non-selected patients, respectively (log-rank test-2.4, p-0.1). Conclusion: In NSCLC with RTD, ICPi have favorable efficacy and independent impact on OS. NSCLC with RTD is associated with MSI stable status and variable levels of PD-L1 expression and TMB; their predictive value remains to be determined.